Kasabach-Merritt syndrome. - Neri, I.; Patrizi, A.; Marzaduri, S.; Morini, S.M.; Cocchi, G. (European Journal of Pediatric Dermatology, 2018)
Kasabach-Merritt syndrome is characterized by an angioma, which is present at birth or occurs in the first months of age, associated with hemorrhagic diathesis and thrombocytopenia, with platelets ranging between 10,000 and 40,000/mm3. This rare syndrome may run a fatal outcome and requires timely therapeutical measures, due to the risk of acute hemorrhage and possible compression of vital organs during the period of rapid growing of the tumor. Systemic steroids, platelet antiaggregants, pentoxifylline and interferon are more frequently used in the treatment of this syndrome. The case here reported did not respond to the medical treatment, leading to the surgical operation.